2022
DOI: 10.1287/mnsc.2021.4209
|View full text |Cite
|
Sign up to set email alerts
|

Experimentation and Start-up Performance: Evidence from A/B Testing

Abstract: Recent scholarship argues that experimentation should be the organizing principle for entrepreneurial strategy. Experimentation leads to organizational learning, which drives improvements in firm performance. We investigate this proposition by exploiting the time-varying adoption of A/B testing technology, which has drastically reduced the cost of testing business ideas. Our results provide the first evidence on how digital experimentation affects a large sample of high-technology start-ups using data that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 74 publications
1
39
0
Order By: Relevance
“…Many did not use it intensively. 2 If experiments work, where does experimentation go wrong? For one, meaningless metrics lead to pointless experiments.…”
Section: Experimentation and Learningmentioning
confidence: 99%
“…Many did not use it intensively. 2 If experiments work, where does experimentation go wrong? For one, meaningless metrics lead to pointless experiments.…”
Section: Experimentation and Learningmentioning
confidence: 99%
“…In fact, applying * Corresponding author. controlled experiments such as A/B testing experiments in business has improved the performance of companies [18]. Also, there are some methodological contributions for optimal design of experiments applied for A/B testing.…”
Section: Instructionmentioning
confidence: 99%
“…Over the past decade, however, the organizational management of experimentation has dramatically changed (Luca & Bazerman, 2021;Van de Poel, Asveld, & Mehos, 2017). Scholars have shown that organizations can now leverage advances in digital technologies (e.g., algorithms, big data analytics, and machine learning) to deploy experiments at scale, in real-time, and at a relatively low cost (Koning, Hasan, & Chatterji, 2022;Marres & Stark, 2020;Zuboff, 2019). This new organizational management of experimentation is particularly salient in digital platform settings.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the impact of experimentation in digital platform settings on worker autonomy is important because most management research focuses on the design and efficacy of experimentation from an organization's vantage point (Engels, Wentland, & Pfotenhauer, 2019;Koning et al, 2022;Luca & Bazerman, 2021). Research has largely overlooked how organizations' use of experimentation impacts less powerful workers (i.e., the experimental subjects) beyond an experiment's pre-defined goal (Marres & Stark, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation